2015
DOI: 10.1002/app.41851
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan/gelatin porous bone scaffolds made by crosslinking treatment and freeze‐drying technology: Effects of crosslinking durations on the porous structure, compressive strength, and in vitro cytotoxicity

Abstract: In this study, freezing was used to separate a solute (polymer) and solvent (deionized water). The polymer in the ice crystals was then crosslinked with solvents, and this diminished the linear pores to form a porous structure. Gelatin and chitosan were blended and frozen, after which crosslinking agents were added, and the whole was frozen again and then freeze-dried to form chitosan/gelatin porous bone scaffolds. Stereomicroscopy, scanning electron microscopy, compressive strength testing, porosity testing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…These cell lines are derived from bone tumors and can display similar properties as osteogenic cells like alkaline phosphatase (ALP) production and mineral deposition . Osteosarcomas have been widely used to investigate the osteogenic suitability of a various range of chitosan-based cross-linked scaffolds. ,,,,,, In the study by Shemshad et al , osteogenic differentiation of MG-63 cells seeded on a TPP cross-linked chitosan scaffold with addition of hydroxyapatite and bioactive silicate diopside is reported . By adding the osteogenic factor strontium to their scaffold, Rodríguez-Méndez et al observed increased ALP activity of MG-63 cells, whereas Pati et al .…”
Section: Cell Encapsulation In Chitosan Cross-linked Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…These cell lines are derived from bone tumors and can display similar properties as osteogenic cells like alkaline phosphatase (ALP) production and mineral deposition . Osteosarcomas have been widely used to investigate the osteogenic suitability of a various range of chitosan-based cross-linked scaffolds. ,,,,,, In the study by Shemshad et al , osteogenic differentiation of MG-63 cells seeded on a TPP cross-linked chitosan scaffold with addition of hydroxyapatite and bioactive silicate diopside is reported . By adding the osteogenic factor strontium to their scaffold, Rodríguez-Méndez et al observed increased ALP activity of MG-63 cells, whereas Pati et al .…”
Section: Cell Encapsulation In Chitosan Cross-linked Scaffoldsmentioning
confidence: 99%
“…188 Osteosarcomas have been widely used to investigate the osteogenic suitability of a various range of chitosan-based cross-linked scaffolds. 93,96,129,133,153,155,165 In the study by Shemshad et al, osteogenic differentiation of MG-63 cells seeded on a TPP cross-linked chitosan scaffold with addition of hydroxyapatite and bioactive silicate diopside is reported. 95 By adding the osteogenic factor strontium to their scaffold, Rodri ́guez-Meńdez et al observed increased ALP activity of MG-63 cells, whereas Pati et al demonstrated the benefits of cross-linking with an increase in mineralization (Figure 9).…”
Section: Osteogenic Lineage Committed Cells In Chitosanmentioning
confidence: 99%
“…FPUFs has been widely used in the field of cushioning and energy absorption due to its lightweight and high specific strength, and its energy absorption effect is one of the indicators for evaluating the cushioning performance [25][26][27]. The energy absorbed by the composite is defined in equation…”
Section: Energy Absorptionmentioning
confidence: 99%
“…Since the test condition was compression, the main EA and specific energy absorption (SEA) of the structure were mainly studied. The total EA δ EA is defined in equation (3).…”
Section: Ea Characteristicsmentioning
confidence: 99%
“…In the past few decades, due to the frequent occurrence of injuries caused by vehicle accidents and sports collisions, energy absorbing materials have become a research hot-topic in the field of protection. Among them, flexible polyurethane foam was one of the most widely used flexible materials in energy absorption (EA) [1][2][3]. Flexible polyurethane foam can basically restore the original size and achieve reuse when subjected to minor compression [4][5][6].…”
Section: Introductionmentioning
confidence: 99%